2005
DOI: 10.21273/horttech.15.4.0739
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with Wastes and Composts in Nursery Substrates

Abstract: During the past 20 years, the Ornamental Nursery Research Program at the former Horticultural Research Institute of Ontario (now part of the University of Guelph) has been conducting applied research dealing with environmentally friendly and sustainable nursery production practices with emphasis on container production. The use of farm, industrial, and consumer waste by-products as amendments in nursery substrates has been a major focus. The program has evaluated hundreds of potting mixes derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 34 publications
2
69
0
2
Order By: Relevance
“…A number of studies have shown that several organic residues such as urban solid wastes, plant wastes, sewage sludges, paper wastes, spent mushroom, coconut coir and even green wastes, after proper composting, can be used with variable results as growing media in lieu of peat (Abad et al, 2005;Chong, 2005;Garcia-Gomez et al, 2002;Maher et al, 2007;Méndez et al, 2011;Ostos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that several organic residues such as urban solid wastes, plant wastes, sewage sludges, paper wastes, spent mushroom, coconut coir and even green wastes, after proper composting, can be used with variable results as growing media in lieu of peat (Abad et al, 2005;Chong, 2005;Garcia-Gomez et al, 2002;Maher et al, 2007;Méndez et al, 2011;Ostos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Peatlands in the northern hemisphere store approximately onethird of world's CO 2 (Gorham, 1991), and there is increasing public concern over their destruction during peat harvest (Barkham, 1993;Robertson, 1993;Zaller, 2007;Blok and Verhagen, 2009;Jayasinghe et al, 2010). The utilization of farm, industrial and consumer waste by-products as components of nursery substrates has been extensively investigated during the past several decades, with a wide variety of materials having been examined (Chong, 2005;Krucker et al, 2010;Vaughn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Saline composts can be successfully improved by using different techniques: (1) by leaching the compost with tap water before growing media preparation (Chen et al, 1984;Lohr et al, 1984;Marfà et al, 1998;Szmidt and Conway, 1995); (2) by leaching the compost when filling up the container with one (or several) starting irrigation(s) (Chong, 2005), or with standard nutrient solution (Mazuela et al, 2005), before transplanting; (3) by leaching the compost-based medium with the customary irrigation programs applied during the crop growing season, especially when using shallow containers (Chong, 2005;Hernández-Apaolaza et al, 2005;Papafotiou et al, 2004); and, (4) by mixing the compost with other nutrient-poor, non-saline materials (e.g. Sphagnum moss peat, pine bark, etc.)…”
Section: Introductionmentioning
confidence: 99%